Avian carcinoma virus MH2 contains a transformation-specific sequence, mht, and shares the myc sequence with MC29, CMII, and OK10 viruses. - Kan, N C (1983)
Avian carcinoma virus MH2 has been grouped together with MC29, CMII, and OK10, because all of these viruses share a transformation-specific sequence termed myc. A 5.2-kilobase (kb) DNA provirus of MH2 has been molecularly cloned. The complete genetic structure of MH2 is 5'-delta gag(1.9-kb)-mht(1.2-kb)-myc(1.3-kb)-delta env(?) and noncoding c-region (0.2-kb)-3'. delta gag, delta env, and c are genetic elements shared with nondefective retroviruses, whereas mht is a unique, possibly MH2 transformation-specific, sequence. Hybridizations with normal chicken DNA and cloned chicken c-myc DNA indicate that the mht sequence probably derives from a normal cellular gene that is distinct from the c-myc gene. The genetic structure of MH2 suggests that the delta gag and mht sequences function as a hybrid gene that encodes the p100 putative transforming protein. The myc sequence of MH2 appears to encode a second transforming function. Therefore, it seems that MH2 contains two genes with possible oncogenic function, whereas MC29, CMII, and OK10 each carries a single hybrid delta gag-myc transforming gene. It is remarkable that, despite these fundamental differences in their primary structures and mechanisms of gene expression, MH2 and MC29 have very similar oncogenic properties.